Assisted activated carbon‐microwave degradation of the sodium dodecyl benzene sulfonate by nano‐ or micro‐Fe3O4 and comparison of their catalytic activity. Issue 2 (30th November 2011) - Zhang, Zhaohong; Xu, Yao; Shen, Manli; Dionysiou, Dionysios D.; Wu, Dan; Chen, Zhonglin; Li, Fangyi; Liu, Danni; Zhang, Fengqiu
<x xml:space="preserve">Abstract</x> An improved method of the integration of activated carbon‐microwave (AC/MW) system with magnetic material such as nano‐ or micro‐Fe3O4 is proposed. A series of experiments to study the Fe3O4 assisted AC/MW (Fe3O4/AC/MW) degradation of sodium dodecyl benzene sulfonate (SDBS), as a model organic contaminant, was performed. The catalytic activities of nano‐Fe3O4/AC and micro‐Fe3O4/AC under MW irradiation were also compared. Some influence factors like added amount of Fe3O4, MW irradiation time, initial SDBS concentration, solution acidity, and Fe3O4/AC dose on the degradation were assessed in detail. The results showed that the addition of Fe3O4 significantly promoted the AC/MW degradation and nano‐Fe3O4/AC displayed higher catalytic activity under MW irradiation. By comparison, the nano‐Fe3O4/AC/MW process exhibited many advantages including high degradation rate, short irradiation time, low cost, no residual intermediates, and no secondary pollution in application. Thus, it shows to be a promising technology for the destruction of organic contaminants in wastewater treatment applications. © 2011 American Institute of Chemical Engineers Environ Prog, 32: 181‐186, 2013